2010
DOI: 10.1186/1471-2466-10-3
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study evaluating the pharmacokinetics, safety and tolerability of repeat dosing with a human IL-13 antibody (CAT-354) in subjects with asthma

Abstract: BackgroundIL-13 has been implicated in the development of airway inflammation and hyperresponsiveness. This study investigated the multiple-dose pharmacokinetics and safety profile of human anti-IL-13 antibody (CAT-354) in adults with asthma.MethodsThis was a multiple-dose, randomised, double-blind, placebo-controlled phase 1 study in asthmatics (forced expiratory volume in 1 second [FEV1] ≥ 80% predicted). Subjects were randomised to receive three intravenous infusions of CAT-354 (1 mg/kg, 5 mg/kg or 10 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 16 publications
3
30
0
1
Order By: Relevance
“…YM-341619 administered orally to rats during OVA-induced allergic inflammation decreased eosinophil recruitment to the lungs, and decreased airway reactivity (17). Antibodies that target IL-13, IL-4, or the IL-4Ra chain of the IL-13R decreased the activation of STAT6, and are currently undergoing human clinical trials to reduce asthma symptoms and mucus production (16,(29)(30)(31)(32)(33). Based on our findings, STAT6-targeted and IL-13-targeted therapeutics may not eliminate the symptoms associated with mucous cell metaplasia and mucus production in patients with asthma and increased IL-17A protein expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YM-341619 administered orally to rats during OVA-induced allergic inflammation decreased eosinophil recruitment to the lungs, and decreased airway reactivity (17). Antibodies that target IL-13, IL-4, or the IL-4Ra chain of the IL-13R decreased the activation of STAT6, and are currently undergoing human clinical trials to reduce asthma symptoms and mucus production (16,(29)(30)(31)(32)(33). Based on our findings, STAT6-targeted and IL-13-targeted therapeutics may not eliminate the symptoms associated with mucous cell metaplasia and mucus production in patients with asthma and increased IL-17A protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined IL-17A mucous cell metaplasia in the absence of STAT6. Understanding this mechanism is important, because therapeutics targeting the STAT6 pathway are being developed for the treatment of asthma (16,17,(29)(30)(31)(32)(33)). These patients demonstrate increased levels of mucus production, but with variable expressions of IL-13 or periostin, an IL-13 marker protein (34), calling into question the absolute IL-13 dependence of airway mucus production in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The selected maximum dose (10.0 mg/kg, IV) for FIH study of CNTO 5825 provided predicted systemic exposures that were below observed systemic exposures at NO-AEL in rats and cynomolgus monkeys. In addition, the selected doses (0.1, 0.3, 1.0, 3.0 and 10.0 mg/kg) of CNTO 5825 for FIH study were within the range of doses that have been evaluated in clinical studies of related anti-IL-13 mAbs [33][34][35][36].…”
Section: Discussionmentioning
confidence: 95%
“…Recently, it was described that a human anti-IL-13 mAb given by intravenous injection or by sub-cutaneous administration displays an acceptable safety profile and can be administered safely in patients with asthma (29,30). Furthermore, lebrikizumab, an anti-IL-13 mAb administered subcutaneously significantly improved lung function in patients with moderatesevere asthma who had elevated serum periostin at baseline (26).…”
Section: Discussionmentioning
confidence: 99%